ANXIETY IN BARBARA PARK'S THE KID IN THE RED JACKET: A PSYCHOANALYTIC APPROACH - DARMANTO, PRIYONO (2010)
The major problem of this study is Howard's disappointment causes him frustration, sad, and negative thinking because of his father who decided to move into a new town without taking a vote. He will miss his old town that he loves much, and his close friends that are always together since preschool. The objectives of the study are to analyze the novel based on its structural elements and to analyze the novel based on Psychoanalytic Analysis. In analyzing The Kid in the Red Jacket the researcher uses qualitative method and psychoanalytic approach. The object of the study is Barbara Park's The Kid in the Red Jacket published in 2001 by Scholastic, Inc New York. The data sources are primary data and secondary data. The primary data source is the novel The Kid in the Red Jacket itself and the secondary data sources are the other sources related to the analysis such as the author's biography, the book of fiction, the book of psychoanalytic, dictionary, virtual references and the other relevant information that support this research. The method of data collection is library research by collecting and recording both of the primary and secondary data. The technique of data analysis used in this study is descriptive analysis. Based on the analysis above, the researcher draws some conclusions as follows: first, the researcher concludes that the elements of the novel present a good unity that consists of exposition, complication, climax, and resolution; second, the anxiety of Howard Jeeter influences his id to do something in his unconsciousness. As the work of ego, Howard Jeeter fulfills the id demand. Nevertheless, his superego can differentiate what is true and false.